Exploration of the Effects of Rural Obstetric Unit Closures on Birth Outcomes in North Carolina. Issue 2 (2nd December 2020) - Sullivan, Margaret H.; Denslow, Sheri; Lorenz, Kathleen; Dixon, Suzanne; Kelly, Emma; Foley, Kathleen A.
Abstract: Purpose: Closures of rural labor and delivery (L/D) units have prompted national and state‐based efforts to assess the impact on birth outcomes. This study explores local effects of L/D closures in rural areas of North Carolina (NC). Methods: This is a retrospective cohort study of birth outcomes of 4, 065 women in 5 rural areas of NC with L/D unit closures between 2013 and 2017. Outcomes were abstracted from birth certificate data from the NC Vital Statistics Reporting System. Localized outcomes 1 year prior to L/D unit closure were compared with outcomes 1 and 2 years post closure, including: (1) birth location and demographics, (2) change in travel patterns for birth, and (3) birth outcomes, including rates of labor induction, cesarean deliveries, maternal morbidity, and neonatal outcomes. Findings: Before closures, 25%‐56% of deliveries occurred outside county of residence. Commercially insured and college‐educated women were more likely to deliver out‐of‐area. Closures increased travel distance to delivery hospital an average of 7‐27 miles. In 2 areas, cesarean delivery rates decreased despite an increase in labor inductions. There was also variability between areas in prenatal care adequacy and breastfeeding. Conclusions: We found that L/D unit closures in rural NC disproportionately affected women on Medicaid. The impact showed area‐specific variability, highlighting effects potentially masked by statewide or national analyses. Implications for future L/D closures would be eased by regional coordination and planning to mitigate negative effects, and state and national policies should address the excess burden placed on vulnerable populations.